A SYSTEMATIC LITERATURE REVIEW ON THE METHODS OF INTERACTIVE ENGLISH LANGUAGE TEACHING USING DIVERSE ONLINE PLATFORMS - Jozua F. Palandi; Zusana E. Pudyastuti (SEAQIL Journal of Language Education, 2023)
Embracing technology in teaching English has become a necessity following the rapid growth of technology, including the mushrooming of the use of e-learning in the ELT context. It has been known that a conventional classroom facilitates and enhances interactive language teaching effectively since the students can communicate with their teacher and classmates through face-to-face meetings. In the era of e-learning, developing interactive language teaching has become a challenge for English teachers. Because e-learning requires students to be more independent, they do not have to study in class with their friends and teachers. On the other hand, students need to interact with others to use English for communication successfully. By employing Systematic Literature Review (SLR), this research reviews some concepts to find suitable methods on how e-learning can accommodate ELT as effectively and interactive as conventional classrooms because finding suitable e-learning methods is important for enabling the students to use English successfully. Finding the best e-learning application that supports e-learning interaction in ELT is another objective of this paper. Moreover, it is expected that the paper will contribute to the development of an e-learning English course as interactive as the teaching of English in the conventional classroom.